대한민국 고속도로를 위한 교통 분석 및 시뮬레이션 시스템 - 한영탁(Young Tak Han); 전수빈(Soo Bin Jeon); 신세정(Se Jeong Shin); 서동만(Dong Mahn Seo); 정인범(In Bum Jung) (정보과학회 컴퓨팅의 실제 논문지, 2016)
선진국에서는 이미 다양한 지능형 교통 시스템(ITS) 기술을 실제 도로에 적용하여 교통 문제를 해결하고 있고 국내에서도 이를 도입하여 많은 교통문제를 완화시킬 수 있을 것으로 전망된다. 하지만 국외 교통 환경에 적용된 기존 ITS 솔루션들을 실제 국내 도로에 적용하였을 때 예기치 못한 문제의 발생으로 많은 비용을 낭비할 수 있다. 본 논문에서는 위의 문제를 해결하기 위해 대한민국 고속도로 분석및 시뮬레이션 시스템인 KHTA를 제안한다. KHTA는 국내 모든 고속도로의 정보를 분석할 수 있을 뿐만 아니라 재현된 국내 교통 환경에서 직접 구현한 ITS 알고리즘을 시뮬레이션하고 결과를 분석할 수 있다. 사용자는 KHTA를 이용하여 실제 도로에 ITS 장비와 시스템을 설치하는 비용을 들이지 않고도 ITS 알고리즘을 국내 도로에 적용했을 때의 기대효과와 부작용을 예측하고 이를 수정 및 보완할 수 있다. KHTA의 기능과 대한민국 도로에 ITS 알고리즘을 적용한 시뮬레이션의 효과를 검증하기 위해 국내 고속도로 전용 Ramp Metering 알고리즘을 구현하고 시뮬레이션을 진행하였다. 실험 결과 약 5분가량의 Total Travel Time이 감소하였고, 기존 정체구간의 일부분이 해소된 것이 확인되었고, 이를 통해 KHTA는 국내 교통 환경에서 ITS 시스템의 시뮬레이션 및 교통 분석을 할 수 있다는 것을 확인 하였다. 그러므로 국내 ITS 시스템 개발 및 분석에 많은 도움이 될 수 있을 것으로 예상한다. Developed countries have already applied variable Intelligent Transportation System (ITS) technologies and have solved many transportation problems. Researchers also expect that ITS solutions can solve the transportation problems of Korean roads, when they are applied to Korean roads. However, since the existing ITS solutions applied in other countries are used for Korean roads without calibration, they will incur unexpected problems and high cost maintenance costs. In this paper, to solve the above problem, we propose the Korean Highway Traffic Analysis tool (KHTA). It not only analyzes all highway information in Korea, but also simulates the ITS algorithm implemented by traffic developers for the Korean highway environment. To test the stability, applicability and efficiency of the KHTA, we developed and analyzed the result of the ramp metering algorithm. The results show that the total travel time was reduced by 5 minutes compared to that without ramp metering, and traffic congestion was decreased. Thus, we confirmed that the KHTA can simulate ITS systems and can analyze the traffic environment in Korean highway. We expect that this tool would be very helpful to develop and analyze ITS systems in Korea. KCI Citation Count: 0